The influence of security perceptions and digital payment usage on the decision to use the BRImo application in Bandar Lampung - Najwa Devana, Aria; Maulana Agung P; M Iqbal Harori (Cita konsultindo, 2026)
BRImo application. The development of digital banking services has encouraged people to rely more on mobile banking applications for financial transactions. Therefore, the security and convenience of online payments are important factors in the user decision-making process. This study uses a quantitative approach with data collection methods through the distribution of online questionnaires to BRImo app users in Bandar Lampung. The data obtained was analyzed using multiple linear regression techniques to determine the extent of the influence of independent variables on usage decisions. The results of the study show that perceptions of security and the use of digital payments have a positive and significant impact on the decision to use the BRImo application. These findings indicate that the higher the sense of security felt by users and the more often they use digital payments, the more likely they are to choose the BRImo application.